Jointly modeling male and female labor participation and unemployment - David H. Bernstein; Andrew B. Martinez (Econometrics, 2021)
The COVID-19 pandemic resulted in the most abrupt changes in U.S. labor force participation and unemployment since the Second World War, with different consequences for men and women. This paper models the U.S. labor market to help to interpret the pandemic's effects. After replicating and extending Emerson's (2011) model of the labor market, we formulate a joint model of male and female unemployment and labor force participation rates for 1980–2019 and use it to forecast into the pandemic to understand the pandemic's labor market consequences. Gender-specific differences were particularly large at the pandemic's outset; lower labor force participation persists.
Keywords: 330; cointegration; general-to-specific modeling; labor force participation; unemployment